Web Programming with PHP and MySQL A Practical Guide - Bramer, Max.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
Introductory textbook covering all the main features of the 'web programming' languages PHP and MySQL together with detailed examples that will enable readers (whether students on a taught course or independent learners) to use them to create their own applications or understand existing ones. A particular focus is the use of PHP to generate MySQL commands from a script as it is executed. Each chapter includes aims, a summary and practical exercises (with solutions) to support learning. Chapters are designed to stand alone as far as possible, so that they can be studied independently of the rest of the text by those with some previous knowledge of the languages. There is a comprehensive glossary of technical terms, together with extensive appendices for quick reference of language features.
Introduction -- PHP Fundamentals -- The PHP Language: Types of Statement -- More About Arrays -- Some Important Functions -- Formatted Print Functions -- Using Files -- User-Defined Functions -- Passing Variables to a PHP Script I -- Passing Variables to a PHP Script II -- PHP in Action: Managing a Members’ Area -- Using a MySQL Database I -- Using a MySQL Database II -- Creating and Updating MySQL Tables -- Using a PHP Script to Manage a MySQL Database -- PHP in Action: Converting Data between Text Files and Database Tables -- Using PHP to View and Edit Database Tables -- PHP in Action: Maintaining a Membership List -- Appendices.
Keywords: Architecture, Computer; Computer programming; Database management; Computer System Implementation; Programming Techniques; Database Management